Protein 4.1B contributes to the organization of peripheral myelinated axons. - Carmen Cifuentes-Diaz (Public Library of Science (PLoS), 2011)
Neurons are characterized by extremely long axons. This exceptional cell shape is likely to depend on multiple factors including interactions between the cytoskeleton and membrane proteins. In many cell types, members of the protein 4.1 family play an important role in tethering the cortical actin-spectrin cytoskeleton to the plasma membrane. Protein 4.1B is localized in myelinated axons, enriched in paranodal and juxtaparanodal regions, and also all along the internodes, but not at nodes of Ranvier where are localized the voltage-dependent sodium channels responsible for action potential propagation. To shed light on the role of protein 4.1B in the general organization of myelinated peripheral axons, we studied 4.1B knockout mice. These mice displayed a mildly impaired gait and motility. Whereas nodes were unaffected, the distribution of Caspr/paranodin, which anchors 4.1B to the membrane, was disorganized in paranodal regions and its levels were decreased. In juxtaparanodes, the enrichment of Caspr2, which also interacts with 4.1B, and of the associated TAG-1 and Kv1.1, was absent in mutant mice, whereas their levels were unaltered. Ultrastructural abnormalities were observed both at paranodes and juxtaparanodes. Axon calibers were slightly diminished in phrenic nerves and preterminal motor axons were dysmorphic in skeletal muscle. βII spectrin enrichment was decreased along the axolemma. Electrophysiological recordings at 3 post-natal weeks showed the occurrence of spontaneous and evoked repetitive activity indicating neuronal hyperexcitability, without change in conduction velocity. Thus, our results show that in myelinated axons 4.1B contributes to the stabilization of membrane proteins at paranodes, to the clustering of juxtaparanodal proteins, and to the regulation of the internodal axon caliber.